Descrição da interlíngua português-espanhol no desempenho de formandos dos Cursos de Turismo e Hotelaria do IFAL – Campus Maceió: o aporte das teorias Linguísticas e pressupostos de ensino-aprendizagem de LE - Beux, Eronilma Barbosa da Silva (2014)
The study describes the interlanguage phenomena found in the data consisting of utterances in Spanish as a foreign language, coming from learners who are students of technological courses of Tourism and Hospitality of the Instituto Federal de Alagoas. The analyzes were developed from the identification of the detected errors and their possible causes - interference, transfers, generalizations of rules and implications of the learners' difficulties to the communicative competence considering the use of the language for professional purposes. We verified the internal variables of the teaching-learning process of foreign languages and the correlations of these variables with some linguistic theories of structuralist, generative, cognitive and functionalist basis, starting from the assumptions made by Saussure (1916), Chomsky (1957), Dik (1968), Hymes (1972), Lakoff (1987), Halliday (1994) and their developments. The theoretical assumptions that supported the analysis are found in studies of contrastive analysis, error analysis and the analysis of interlanguage of Lado (1957), Corder (1967, 1971) e Selinker (1972, 1991). The methodology consisted of the collection and descriptive-analytical and quantitative analysis of the data recorded on digital audio and video. The results of the analysis show that it is in the lexical level where the learners' largest quantitative errors are concentrated. The analysis of grammatical and phonetic-phonological aspects confirms that the elements that are common to the mother tongue of the learners and the target language tend to promote more failures and errors. It was found that the dimensions of the interlanguage related to interference and transfer as strategy to compensate for the lack of knowledge correspond to processes of cognitive basis, since language learning corresponds to the learning of skills and is not necessarily the result of innate ability. The data show that the interlanguage of each learner is an approximate system of the target foreign language, a result of the skills and experiences of each one in particular and in this specific case, shows that what could be considered interlanguage is quite nascent, pointing thus to the need for revision of curricula aimed at FL as specialized language.